Equity and LLMs in Computing Education: A gradeless perspective under well-being lens - Bispo Jr., Esdras L.; Santos, Juliana M. O. (Anais do Workshop Uma Tarde na Urca: Encontro Filosófico sobre Informática na Educação (URCA); 2024: Anais do I Workshop Uma Tarde na Urca: Encontro Filosófico sobre Informática na Educação, 2024)
There are equity challenges in computing education when we realize that the digital divide expands itself due to the emergence of Large-Language Models (LLMs). Assessment is one of them, provoking computing educators to reflect on their day-to-day practice and reframing their perspectives about LLM use and their own assessment process. This provocative essay brings the gradeless approach as a possibility to deal with computing students’ well-being and, as a consequence, equity in assessment involving LLM scenarios.